Efektivitas Mindfulness Based Cognitive Therapy Untuk Mereduksi Compassion Fatigue Mahasiswa PIAUD - Ulfa; Prassasty, Anna; Fuadina, Nabila (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
This study tested the effectiveness of mindfulness-based cognitive therapy (MBCT) on reducing Compassion fatigue in post-primary school students using a quasi-experimental method with a pretest-posttest control group design. The study sample consisted of 20 participants divided into an experimental group (n=10) receiving 6 sessions of MBCT intervention and a control group (n=10) participating in regular discussions. Data analysis was conducted using a paired sample test to evaluate differences in scores within groups so that results could be compared between groups. The results of the statistical test showed a significant difference in the experimental group based on the results of the paired samples test, the experimental group (M = -21,600, SD = 3,777, t = -18,084, p = .000) in the control group (M = -900, SD = 3,213, t = -.886, p = .399. This finding is also supported by reflective questions in supporting and strengthening the results of quantitative data, participants reported an increase in realizing emotions and feeling calmer after treatment. This study provides empirical evidence that MBCT is effective as an intervention to reduce Compassion fatigue in PIAUD students as prospective educators. Further research recommendations are suggested to develop a Compassion fatigue scale specifically for educators and can be implemented for other psychological scales with different subjects and can use more comprehensive research methods.